Disentangling single-particle and collective signatures in 12C(p,2p)11B reaction - E. Cravo; R. Crespo; A. Deltuva; D. Jurčiukonis (Physics Letters B)
We calculate kinematically fully exclusive cross sections for the 12C(p,2p)11B reaction at Ep=98.7 MeV proton beam energy, leading to the low-lying states of 11B. We use rigorous three-particle scattering framework extended to include simultaneously and consistently both core excitation and single-particle-like excitations. This predicts significant cross sections for the transitions to the final 52− (4.45 MeV) and 72− (6.74 MeV) excited states that cannot be populated through the direct single-particle excitation mechanism. We show that these two types of excitations manifest themselves with distinct and characteristic features in the scattering observables.